Popular Hymnody and Lived Catholicism in Hungary in the 1970s–1980s - Povedák, Kinga 1979- (2021)
In this article, I look at how popular hymnody and the surrounding devotional and liturgical practices changed after the Second Vatican Council in Hungary. The songs amongst authoritarian, atheistic circumstances sounded astonishingly similar to the emerging “folk mass movement”. The discourse analysis of Hungarian popular hymnody contributes to a new perspective of Eastern European Catholicism and helps us understand how “lived Catholicism” reflects the post-Vatican spirit. Post-Vatican popular hymnody, a catalyst for a new style of devotional practices, is understood as “performed theology” behind the Iron Curtain expressing relationality, as it actualizes and manifests spiritual, eschatological, and ecclesial relationships.
Keywords: Christian popular music; “beat mass”; popular hymnody; post-conciliar liturgical music